Efecto de la pandemia del COVID-19 en el sector arrocero de America Latina y el Caribe - CGIAR Research Program on Rice (2021)
The study assesses the qualitative effects of COVID in the region. The title in English is: COVID-19 Effects in the rice sector in Latin America and the Caribbean